Cover Image, Volume 43, Issue 8. (11th June 2019) - Lei, Mingzhun; Song, Yuntao; Liu, Sumei; Lu, Kun; Xu, Shuling; Xu, Kun
Abstract : The back cover image is based on the Research Article Conceptual design of the HCCB blanket system integration for CFETR by Mingzhun Lei et al., https://doi.org/10.1002/er.4467 .